Ethical self-regulation systems for Non-Governmental Organizations (NGOs) - Mario Aguiló; Jordi Longás Mayayo; Irene Saavedra Robledo (Sociedad Iberoamericana de Pedagogía Social, 2014)
The article presents the theoretical results of a study focusing on self-regulatory systems as the evaluative approach to the ethical performance of NGOs. Its aim is to analyse the current self-regulatory systems in NGOs in order to report their scope, identify the evaluative dimensions and variables used, and clarify their role in relation to other strategies and other apparently similar resources, such as quality control systems. From the literature survey and content analysis of the major databases and institutional documents of authors and managers of various self-regulatory systems, the current practices are described, compared and analysed. The results lead us to conclude that through self-regulation, primarily codes of conduct and certifications of good practices, a growing number of organizations are developing standards and shared rules of conduct to address and channel the emerging demand for transparency and accountability to their stakeholders. However, there is great disparity in the way they are used, along with their geographical distribution and content. Finally, we offer an integrative proposal of the different variables used to evaluate ethical management in the leading certification systems analysed.